2021
DOI: 10.1097/cce.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of an Interdisciplinary Treatment Approach to Optimize Recovery From Critical Coronavirus Disease 2019

Abstract: OBJECTIVES: Examine the safety and feasibility of a multimodal in-person or telehealth treatment program, administered in acute recovery phase for patients surviving critical coronavirus disease 2019. DESIGN: Pragmatic, pre-post, nonrandomized controlled trial with patients electing enrollment into one of the two recovery pathways. SETTING: ICU Recovery Clinic in an academic medical center. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 65 publications
(86 reference statements)
1
17
0
Order By: Relevance
“…An important nding of the present study is the great improvement in functional capacity after supervised combined exercise training, corroborating others with similar protocols and outcomes [27][28][29][30][31][32]. The handgrip strength increased in our study ~ 32,7% post-COVID rehabilitation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…An important nding of the present study is the great improvement in functional capacity after supervised combined exercise training, corroborating others with similar protocols and outcomes [27][28][29][30][31][32]. The handgrip strength increased in our study ~ 32,7% post-COVID rehabilitation.…”
Section: Discussionsupporting
confidence: 90%
“…This result presented a higher improvement when compared to Mayer et al [31] study, that evaluated handgrip strength after 8-week moderate-intensity rehabilitation and observed an improvement of ~ 15,1% and Nambi et al [32] with post-COVID sarcopenic patients in which observed improvement of ~ 10,9% after 8-week low-intensity rehabilitation. This magnitude difference probably occurred due Mayer et al [31] performed an ICU recovery previous to outpatient rehabilitation and Nambi et al [32] analyze community-dwelling elderly with post-COVID, and both studies had higher baseline values than compared to present study. About STS, De Souza et al [28] showed a signi cant improvement after 6-week home-based rehabilitation (~ 53,5%).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Patients were excluded if they had a hospitalization in last 12-months or history of COVID-19. At the baseline testing, there were no missing data for patients enrolled in the study. Nineteen (critical-COVID) and 9 (severe-COVID) patients included in this study were co-enrolled in a nonrandomized rehabilitation intervention cohort study 36,37 and thus had data available at two-time-points (1-month and 3-months post discharge). Patients were excluded from all three groups if they had an acute or chronic neurologic, neurodegenerative, or orthopedic condition or disease that influenced cognition or motor performance.…”
Section: Methodsmentioning
confidence: 99%
“…COVID-19 promoted innovative approaches such as telemedicine and virtual reality [75]. As an example, the out-patient clinics for long-COVID-19 or cognition improvement are promising [76,77], as they provide multidisciplinary and personalised care [78,79]. Longterm symptoms are being evaluated in multicentric studies aiming to recruit 10 000 patients (CO-FLOW and PHOSP-COVID) [80,81].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%